Kolaborasi Guru PAI dan Orang Tua dalam Membina Sikap Spiritual Siswa di Era Modern - Isrofuzain, Isrofuzain; Subando, Joko (TSAQOFAH, 2026)
The growing challenges of globalization and technological development in the modern era require students to possess strong spiritual attitudes in facing the dynamics of everyday life, making synergistic education between school and family increasingly important. This study aimed to explore the role of collaboration between Islamic Religious Education (PAI) teachers and parents in fostering students’ spiritual attitudes in the modern era. A qualitative approach was employed, with data collected through in-depth interviews and observations of interactions among teachers, parents, and students in the context of spiritual development. The findings show that effective collaboration between teachers and parents can enhance students’ spiritual awareness by strengthening religious values consistently across school and home environments, through intensive communication, role modeling, and continuous guidance. The study concludes that structured and sustainable cooperation between PAI teachers and parents has a significant impact on the formation of students’ spiritual character. Practically, these findings offer insights for educators and parents to optimize their respective roles in designing more integrated spiritual education strategies that are relevant to the demands of the modern era.